2012
DOI: 10.1159/000341898
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Difficult’ Polyp: Pitfalls for Endoscopic Removal

Abstract: Adenomatous polyps are early neoplasias of colorectal cancer (adenoma-carcinoma sequence). The majority of adenomas or early invasive cancers (T1sm1) can be resected by endoscopy. Endoscopic resection techniques include classic loop polypectomy, endoscopic mucosectomy with preceding lifting of the (almost flat) lesion, endoscopic submucosal dissection and transanal microsurgical resection, an alternative to endoscopic submucosal dissection in the rectum. Endoscopic polyp removal should always aim to resect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
(31 reference statements)
0
7
0
1
Order By: Relevance
“…The edges of the polypectomy site should be carefully assessed and any residual polyp tissue should be completely removed; argon plasma coagulation or cautery with the snare tip are particularly useful for this purpose. If an SSP does not lift when performing injection techniques, it may be due to scarring from previous attempts at resection, or it may be an indication of invasive cancer and sampling may be prudent [53]. The decision of whether to undertake endoscopic resection of SSPs will ultimately depend on the lesion’s characteristics and the endoscopist’s skill level, but almost all lesions can safely be removed endoscopically with surgical resection rarely being required.…”
Section: Eradicationmentioning
confidence: 99%
“…The edges of the polypectomy site should be carefully assessed and any residual polyp tissue should be completely removed; argon plasma coagulation or cautery with the snare tip are particularly useful for this purpose. If an SSP does not lift when performing injection techniques, it may be due to scarring from previous attempts at resection, or it may be an indication of invasive cancer and sampling may be prudent [53]. The decision of whether to undertake endoscopic resection of SSPs will ultimately depend on the lesion’s characteristics and the endoscopist’s skill level, but almost all lesions can safely be removed endoscopically with surgical resection rarely being required.…”
Section: Eradicationmentioning
confidence: 99%
“…In addition, the stalk diameter is also a significant risk factor for PPB in large pedunculated polyps [32]. Generally, there are nourishing blood vessels in the stalk of the pedunculated polyps, and the size of blood vessels depends on the size of polyp and the diameter of stalk [29,33]. Our study re-confirmed that polyp size ≥20 mm and stalk diameter ≥ 4 mm were significant predictors of immediate PPB compared with polyp size < 19 mm and stalk diameter < 3 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Buradan yola çıkarak "zor" kolorektal polip tanımlaması yapılmıştır. Lezyonun boyutu, şekli, yerleşimi veya önceden yapılmış girişim nedeniyle oluşan fibrosis varlığında endoskopik olarak çıkarılmasının güç olduğu düşünülen polipler "zor" kolorektal polip olarak adlandırılmıştır (3) .…”
Section: Introductionunclassified